Antarctic Gateway Ports: Opening Tourism to Macquarie Island and the East Antarctic from Hobart - Muir, S; Jabour, JA; Carlsen, J (Tourism in Marine Environments, 2007)
This article discusses the significance of Antarctic gateway ports, and identifies the key issues and challenges in developing East Antarctic tourism, especially through the port of Hobart. Recent opportunities have emerged through increased ship-borne and pending air-borne capacity from Hobart, and a network of government and private agencies have made Hobart the locus of these services. This presents an opportunity to investigate the needs and expectations of tourists through the gateways with a view to developing products and services to meet those needs and expectations. Findings from a preliminary survey of East Antarctic tourists in the 20052006 season are presented and a model for developing tourism to the East Antarctic from Hobart is proposed.